2015
DOI: 10.1002/stem.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotency Activity of Nanog Requires Biochemical Stabilization by Variant Histone Protein H2A.Z

Abstract: The variant histone protein H2A.Z plays a critical role in early development. Likewise, Nanog, a master regulator of embryonic stem cells (ESCs), is essential for proper development in early embryogenesis. In this study, we establish that these two factors work together to maintain pluripotency. It is shown that H2A.Z influences the protein level of Nanog through the ubiquitin-proteasome pathway. Knockdown of H2A.Z causes differentiation of mouse ESCs and disrupts the reprogramming of somatic cells, which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…This analysis supports the existence of interactions between Chd4 and H2A.Z at the chromatin level. Intriguingly, a role of H2A.Z for inhibition of Nanog protein degradation through the ubiquitin-proteasome pathway was previously observed (47). Therefore, stabilizing proteins encoded by pluripotency-associated genes could be one of the important mechanisms by which H2A.Z sustains ESC self-renewal.…”
Section: Discussionmentioning
confidence: 86%
“…This analysis supports the existence of interactions between Chd4 and H2A.Z at the chromatin level. Intriguingly, a role of H2A.Z for inhibition of Nanog protein degradation through the ubiquitin-proteasome pathway was previously observed (47). Therefore, stabilizing proteins encoded by pluripotency-associated genes could be one of the important mechanisms by which H2A.Z sustains ESC self-renewal.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, H2A.Z has been reported to interact with Nanog, another key pluripotency factor, and to stabilize Nanog protein levels in mESCs. Moreover, KD of H2A.Z induces differentiation of mESCs [54]. Further studies of pioneer factors, histone variants and histone modifications will help illustrate the mechanistic interplay between them.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies suggested the relevance of H2A.Z in diverse biological phenomena including DNA repair (Nishibuchi et al 2014), development (Clarkson et al 1999;Faast et al 2001), cell differentiation (Creyghton et al 2008), gene reprogramming (Wang et al 2015), tumorigenesis (Hua et al 2008;Vald es-Mora et al 2012;Kim et al 2013), and cognate memory (Zovkic et al 2014). H2A.Z is essential for the development of Drosophila and mice (Clarkson et al 1999;Faast et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…H2A.Z is essential for the development of Drosophila and mice (Clarkson et al 1999;Faast et al 2001). It also plays important roles in differentiation and pluripotency of mouse ES cells (Creyghton et al 2008;Wang et al 2015). Furthermore, H2A.Z has been reported to regulate gene expression by recruiting polycomb group proteins during ES cell differentiation (Creyghton et al 2008) and known to contribute to pluripotency of ES cells by binding to Nanog, a master regulator of embryonic stem cells (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%